SPEECHLESS integrates brassinosteroid and stomata signalling pathways - Gudesblat, Gustavo Eduardo (2012)
Stomatal formation is regulated by multiple developmental and environmental signals, but how these signals are integrated to control this process is not fully understood. In Arabidopsis thaliana, the basic helix-loop-helix transcription factor SPEECHLESS (SPCH) regulates the entry, amplifying and spacing divisions that occur during stomatal lineage development. SPCH activity is negatively regulated by mitogen-activated protein kinase (MAPK)-mediated phosphorylation. Here, we show that in addition to MAPKs, SPCH activity is also modulated by brassinosteroid (BR) signalling. The GSK3/SHAGGY-like kinase BIN2 (BR INSENSITIVE2) phosphorylates residues overlapping those targeted by the MAPKs, as well as four residues in the amino-terminal region of the protein outside the MAPK target domain. These phosphorylation events antagonize SPCH activity and limit epidermal cell proliferation. Conversely, inhibition of BIN2 activity in vivo stabilizes SPCH and triggers excessive stomatal and non-stomatal cell formation. We demonstrate that through phosphorylation inputs from both MAPKs and BIN2, SPCH serves as an integration node for stomata and BR signalling pathways to control stomatal development in Arabidopsis.